2011
DOI: 10.2139/ssrn.1916769
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Listing and Pricing Efficiency: The Informational and Anchoring Role Played by the Reference Price

Abstract: When a firm cross-lists its shares in segmented markets, the price of the first issued share, as a reference, plays both an informational and anchoring role in pricing the second issued share. We develop a model illustrating the dual-role. Empirically, we examine a group of Chinese firms that first issue foreign shares and then domestic A-shares, for which the anchoring effect adds to the Ashare underpricing. Consistent with the model predictions, we find that the A-share underpricing is positively related to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…The study implies that, when implementing a momentum strategy, foreign investors should rely on past experience with a certain stock, not on how much they previously owned. Chang et al (2013) confirmed the informational and anchoring role played by the reference price of the first issued share from a firm cross-listing its share in a segmented market. Closely related, Bucchianeri and Minson (2013) find evidence for anchoring in the US real estate market.…”
Section: Survey Of Empirical Studiesmentioning
confidence: 58%
“…The study implies that, when implementing a momentum strategy, foreign investors should rely on past experience with a certain stock, not on how much they previously owned. Chang et al (2013) confirmed the informational and anchoring role played by the reference price of the first issued share from a firm cross-listing its share in a segmented market. Closely related, Bucchianeri and Minson (2013) find evidence for anchoring in the US real estate market.…”
Section: Survey Of Empirical Studiesmentioning
confidence: 58%
“…Research on anchoring and insufficient adjustment has repeatedly demonstrated that there is insufficient adjustment up or down from a starting position and exposure to even irrelevant numbers makes individuals' subsequent quantitative judgments assimilate to the anchor. Anchoring has been shown to have a considerable effect on buyer-seller negotiations where final outcomes are highly correlated with first offers (Galinsky & Mussweiler, 2001) and is present in a wide range of literatures, including those on: financial transactions (Chang et al, 2013); For example, Property problems. Irish Times.…”
Section: Introductionmentioning
confidence: 99%
“…Those investors who overcome these investment barriers can enjoy more stock price premiums. As for Chinese evidence, Chang et al (2013) and Busaba et al (2015) investigated firms that list overseas first and then cross-list on the mainland market, documenting that although these fi rms have inferior post-cross-listing performance, they enjoy infl ated prices and favorable terms.…”
Section: Introductionmentioning
confidence: 99%